Elementos traza de importancia nutricional y toxicológica: biotransferencia desde matrices ambientales a alimentos de origen animal - Arellano, F. (2021)
In Argentina, animal production takes place in several regions where water and soil quality are affected by the occurrence of trace elements both of natural or anthopogenic origin, which may be transferred to the food chain. Their presence may have a negative impact in both animal production and health and may be a risk to human health. Biotransference analysis (BTF), bioaccumulation and exposition risk determination are analytical tools that enable the estimation of the possible impact of trace elements on food quality and health risk for consumers. In Centro de Estudios Transdisciplinarios del Agua (CETA, UBA) and Instituto de Investigaciones en Producción Animal (INPA, CONICET-UBA), our research team has studied the occurrence of trace elements of nutritional significance (i.e. Cu, Fe, Mn) as well as toxicological relevant (i.e, As, Cr, Pb) in animal drinking water, forage and soil and their biotransference to animal food, such as meat, milk and derivatives. Our investigations focus on As, because of the high concentrations registered in groundwater in areas destinated to animal production. The aim of the present review is to analyse the main results obtained sence 2002 on the occurrence of specific trace elements in the environment (water, food, forage) and animal food, and their biotransference to human food with possible risk for consumers.